Do university-educated families lose their edge as education expands? The withering performance and advantage of their children. - Valdés, Manuel T; Bernardi, Fabrizio; Lievore, Ilaria (Social Forces, 2026)
Extensive research has examined the effect of educational expansion in one cohort on educational inequality and occupational returns in that same cohort. This study makes a novel contribution by exploring whether the expansion of university education among parents affects their children's academic achievement. We argue that this expansion reduces the selectivity of university attainment, making graduates progressively less selected on traits relevant to their children's achievement. Additionally, expansion likely diminishes occupational returns on a university degree, increasing the proportion of overqualified university-graduated parents. Consequently, the average achievement of children from university-educated families should diminish with this expansion among parents. Using data from 30 countries across seven waves of the Program for International Student Assessment, we show that students from university-educated families experience a notable decline in achievement as the proportion of university-educated parents increases. Importantly, the growing over-qualification of university-educated parents and the diminishing objectified cultural capital of university-educated families mediate this negative effect. Furthermore, we also observe a negative association between educational expansion among parents and children's achievement in non-university-educated families, but less pronounced, resulting in a negative (albeit modest) association between expansion among parents and inequality among children.